Capital Flight and War - Davies, Victor A.B. (World Bank, Washington, DC, 2012)
The author provides empirical evidence on the effects of inflation on post-war capital flight flows. He tests the hypothesis that inflation has a positive additional impact on capital flight flows after war. He uses a new panel dataset of 77 developing countries, of which 35 experienced at least one episode of war between 1971 and 2000. The author uses a range of estimation methods and four capital flight measures-Cline, World Bank Residual, Morgan Guarantee, and Dooley. The results consistently support the research hypothesis: Post-war inflation increases annual capital flight flows by about 0.005 to 0.01 percentage points of GDP. This effect is substantial in total at high inflation rates. The implication is that low inflation helps to curb capital flight in post-conflict economies.